Lethal and intentional violent crimes against women in Alagoas, Northeast Brazil: a comparative study before and during the Covid-19 pandemic - Danielle Nascimento Nunes; Priscila Cavalcante Rodrigues Figueredo; Talita Amaral Vitoriano; Gleice Kelly Ramos Silva Santos; Cecilia Maria Lima de Albuquerque; Thaís Silva Matos; Diogo Uester Silva Matos; Rodrigo Feliciano do Carmo; Carlos Dornels Freire de Souza (BMC Women's Health)
Abstract Background The death of women as a result of violent crime has become a major social and health problem worldwide. Most of these crimes are committed by their partners. The Covid-19 pandemic seems to have amplified the problem, given that measures to contain the spread of the disease have exposed women to more prolonged contact with their aggressors. Objective To describe the epidemiological profile of lethal and intentional violent crimes committed against women in the state of Alagoas, Brazil, from March 2018 to February 2020 (before the pandemic) and from March 2020 to December 2021 (during the first two years of the Covid-19 pandemic). Methods This is an observational study involving all deaths of women due to lethal and intentional violent crimes. The data was obtained from the Alagoas State Secretariat for Public Security. The variables age, type of crime, means used, day of the week and time of the crime were analyzed. The specific mortality rate was calculated for the entire study period. Population data was obtained from the Brazilian Institute of Geography and Statistics (IBGE). Descriptive statistics were used to analyze the data. Results There were 316 deaths during the study period. The mortality rate in 2020 (5.33/100,000) was higher than in the years prior to the pandemic (3.88/100,000 in 2018 and 4.84/100,000 in 2019). There was a predominance of the 18–29 (31.31%) and 30–39 (27.95%) age groups in both periods. The proportion of female homicides was 55.19% in the pre-pandemic period and 64.20% in the pandemic period. The proportion of beating deaths was 1.7 times higher in the pandemic period than in the non-pandemic period (15.23% vs. 8.97%). There was also an increase in beatings on Saturdays, with a proportion 1.60 times higher than in the pre-pandemic period (19.75% vs. 12.34%). Conclusion The victims were predominantly young women, the crimes classified as homicides and with the use of firearms. The study emphasizes that the context of the Covid-19 pandemic may have contributed to the increase in violent crimes against women in Alagoas, highlighting the urgency of preventive measures and support for victims.